Integration of UTAUT2 and Information System Success Model: The Role of User Satisfaction and Financial Literacy Moderation in the Use of Digital Financial Services in Indonesia - Ifan Wicaksana Siregar; Munir; Ade Sobandi; Chairul Furqon (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid development of digital financial services has driven the high adoption rate of financial applications in Indonesia. However, the increase in use is not always accompanied by an adequate level of financial literacy, raising questions about the main determinants of digital financial system usage behavior. This study aims to test the expanded technology acceptance model by integrating the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and information system success model, as well as evaluating the role of user satisfaction and financial literacy in driving the actual use of digital financial services. This study uses a quantitative approach with a cross-sectional design. Data was collected through a survey of active users of digital financial services in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research model examines the influence of UTAUT2 constructs on behavioral intention, the continued relationship between behavioral intention, user satisfaction, and system use, and the role of financial literacy moderation in the relationship between intention and system use. The results of the analysis show that behavioral intention has a significant effect on user satisfaction and system use. Furthermore, user satisfaction has proven to be the most powerful determinant of the actual use of the system, beyond the direct influence of behavioral intention. In contrast, financial literacy has not been shown to moderate the relationship between behavioral intention and system use, suggesting that ease of use and user experience have a more dominant role than formal financial literacy levels in the context of modern digital financial services. The research model has a high ability to explain the variation in user satisfaction and system usage. This research contributes to the development of the technology adoption literature by integrating pre-adoption and post-adoption perspectives in one comprehensive conceptual framework. In practical terms, these findings emphasize the importance of improving the quality of experience and user satisfaction as the main strategy to encourage the sustainability of the use of digital financial services in Indonesia.